Produção de ferrita de cobalto pelo método sol-gel para aplicação em carreamento de óleo - Pimenta, Patrícia Figueirêdo Santos (2017)
Ferrites are ceramic materials with different structural combinations and chemical compositions, which depend on the method of production and assigns to the material a variety of applications. The inverse spinel type ferrites have a centered cubic crystalline structure, composed of divalent ions positioned at octahedral sites, and by trivalent ions that are distributed equally in the tetra and octahedral sites. They are ferrimagnetic materials, composed of grains with small dimensions and adsorptive capacity, which are necessary characteristics for application in the procedure of carrying oil. Cobalt ferrites produced by the GIPM (Interdisciplinary Materials Research Group) were used in an oil loading test based on the adsorption of the oil on the ferrite surface and the drag made by applying a magnetic field, in order to relate the conditions of Ferrite with the amount of oil adsorbed and hauled. From the optimum point of oil transport, new samples of ferrite were produced. The production of the ferrites was performed by the sol-gel method, catalyzed by a solution containing pectin from the orange peel albedo and extracted in the laboratory by the aqueous solution heating method. The ferrites underwent isothermal treatments in a muffle, varying in time and temperature. After the production, the ferrites were characterized by Fourrier Transform Infrared spectroscopy, X-ray diffractometry, Mössbauer spectroscopy and laser diffraction (Malvern). From the characterization of the ferrites, it was observed that with the increase of the temperature of production, there was growth of the crystal and increase of its purity. The cobalt ferrite (CoFe2O4) produced at 12 h and 1073 K showed better efficiency for the application in oil transport, which is intrinsic in its structural characteristics coming from the conditions of preparation of the samples. The temperature factor had greater influence than the time factor In the production of the material to obtain the variable response (mass of oil carried).